Macroeconomic Fluctuations in Developing Countries : Some Stylized Facts - McDermott, C. (IMF Working Papers; Working Paper, 1999)
This paper documents the main stylized features of macroeconomic fluctuations for 12 developing countries. Cross-correlations between domestic industrial output and a large group of macroeconomic variables (including fiscal variables, wages, inflation, money, credit, trade, and exchange rates) are presented. Also analyzed are the effects of industrial country economic conditions on output fluctuations in these countries. The robustness of the results is examined using different detrending procedures. The results indicate many similarities between macroeconomic fluctuations in developing and industrial countries (procyclical real wages; countercyclical variation in government expenditure) and some important differences (countercyclical variation in the velocity of monetary aggregates).